Yankee Twang : Country and Western Music in New England - Murphy, Clifford R. (Book collections on Project MUSE., 2014)
Merging scholarly insight with a professional guitarist's keen sense of the musical life, 'Yankee Twang' delves into the rich tradition of country and western music that is played and loved in the mill towns and cities of the American northeast. Clifford R. Murphy draws on a wealth of ethnographic material, interviews, and encounters with recorded and live music to reveal the central role of country and western in the social lives and musical activity of working-class New Englanders.